Enhanced enzymatic hydrolysis and methane production from rubber wood waste using steam explosion. (1st April 2019) - Eom, Tokla; Chaiprapat, Sumate; Charnnok, Boonya
Abstract: Rubber wood waste (RW) requires due to its recalcitrance a pretreatment step before efficient biochemical conversion is possible. Non chemical steam explosion pretreatment was adopted to enhance enzymatic hydrolysis and anaerobic digestion with severity from 2.70 to 4.35. RW treated at severity 4.35 (214 °C for 10 min) gave the highest 83.9 L CH4 /kgVS effectiveness in anaerobic digestibility together with 45.2% hydrolysability in terms of glucan conversion. The intense pretreatment decreased particle size and degraded most of the hemicellulose, resulting in increased specific surface and better access for enzymes to cellulose. Additionally, the energy yield of steam exploded RW was enhanced by combined enzymatic hydrolysis with anaerobic digestion, in comparison to enzymatic hydrolysis or anaerobic digestion alone. This allowed for an efficient steam explosion pretreatment with co-production of sugar and methane. This study provides a technical approach for efficient biofuel production from RW after steam explosion pretreatment. Valorization of lignin-rich residue generated from the integrated process may increase value of RW, but assessing this requires further study. Graphical abstract: Image 1 Highlights: Rubber wood waste is a potential feedstock for production of sugar and methane. Steam explosion mainly attacked hemicellulose in wood and increased accessible area. Decrease in hemicellulose content was the main reason in enhancing digestibility. Combined enzymatic and anaerobic digestion is proposed for biofuel production.